Juvenile idiopathic arthritis: clinical case - I. V. Zorin; A. L. Frolenko; G. K. Karymova; D. S. Mesyats; Z. T. Alsheeva (Лечащий Врач)
Background. Juvenile idiopathic arthritis (JIA) is an arthritis of unknown cause, lasting more than 6 weeks, developing in children under the age of 16 years with the exclusion of other joint pathology. The incidence of JIA ranges from 2 to 16 per 100 thousand children under the age of 16. The prevalence of JIA in different countries ranges from 0.05 to 0.6%. On the territory of the Russian Federation, the prevalence of JIA in children under 18 years of age reaches 62.3 per 100 thousand children, the primary incidence is 16.2 per 100 thousand, including adolescents, respectively, 116.4 per 100 thousand. children's population and 28.3 per 100 thousand children's population, children under 14 years of age — 45.8 per 100 thousand children's population and 12.6 per 100 thousand children's population. Girls get sick more often. In the etiology of JIA, a combination of various exogenous and endogenous damaging factors and hypersensitivity of the body to their effects plays a role. Pathogenetically, as a result of the presentation of a foreign antigen to T-lymphocytes, activation and proliferation of T-lymphocytes occur with the production of proinflammatory cytokines (IL-1, IL-6, IL-8, IL-17, tumor necrosis factor α, etc.). Macrophages, activated fibroblasts, synoviocytes are also involved in this process, which causes a cascade of pathological changes with the development of progressive inflammation in the joint cavity and systemic manifestations of the disease, resulting in the transformation of acute immune inflammation (characteristic of the early stage of juvenile arthritis) into chronic with the development of pannus and irreversible destruction of joint structures. Involvement of the B-cell link of the immune system leads to the production of a large number of autoantibodies, stimulation of eosinophils and mast cells, as well as the development of allergic reactions. The main clinical manifestation of JIA is progressive gradual destruction of joints, which is often accompanied by extra-articular manifestations, such as fever, rashes, lymphadenopathy, weight loss, which disrupts the growth and development of the child, negatively affects the quality of life. Juvenile arthritis is one of the most frequent and most disabling childhood rheumatic diseases. Objective. This article presents a clinical case of juvenile idiopathic arthritis in a 15-year-old child.Results. The data of clinical and paraclinical examination of the patient, medical documentation, scientific literature were analyzed. Modern approaches to the management of pediatric patients with this pathology are presented. The peculiarity of this clinical case is the debut at 5 years old, which is prognostically unfavorable, high laboratory activity of the process, high risk of structural progression of the disease, impossibility of diagnosis according to the international classification of diseases of the tenth revision. The difficulty of the clinical case is the difficulty of achieving stable remission, which is based on the ineffectiveness of therapy with sulfasalazine, sulfasalazine + methotrexate, adalimumab + methotrexate, adalimumab, golimumab.Conclusion. It turned out to be possible to achieve stable remission only with the help of therapy with secukinumab (cosentix), prescribed by off label, against the background of therapy, which achieved a reduction in pain syndrome, a decrease in the degree of activity of arthritis, a decrease in laboratory markers of inflammation, improvements in the clinical and radiological picture, restoration of the volume of movements in the joints and improvement of the patient's functionality, a significant improvement in well-being and quality patient's life.